Stolen generations : the way forward - Healey, Justin (Thirroul, N.S.W. : Spinney Press, 2009)
"Since the recent Rudd Government apology to Indigenous Australians over past welfare policies of forced removal of children, debate has continued over how to move beyond symbolism with practical measures aimed at healing the traumatic effects of historic wrongs and ameliorating Indigenous disadvantage. This book explores the history of Reconciliation and the Stolen Generations, and includes personal stories of removal and reactions to the apology. It also looks ahead and examines the debate over proposals to act on recommendations from the Bringing Them Home report which urges dealing with unfinished business, including monetary compensation and programs aimed at redressing disadvantage. Is saying sorry enough?"--Provided by publisher
Includes index.
Bibliography: p. 43.
For secondary school age.
Keywords: Stolen generations (Australia); Children, Aboriginal Australian -- History; Children, Aboriginal Australian -- Government policy -- Australia; Government liability -- Australia; Aboriginal Australians -- Removal; Aboriginal Australians, Treatment of; Politics and Government - National symbols and events - Apologies - Stolen generations; Race relations - Reconciliation; Child welfare - Child / parent separation - Stolen generations; Education - Teaching - Materials; Child welfare - Child / parent separation - Stolen generations - Compensation; Politics and Government - National symbols and events - Apologies; Australia